2021
DOI: 10.1371/journal.pone.0250149
|View full text |Cite
|
Sign up to set email alerts
|

Estimating COVID-19 cases in Makkah region of Saudi Arabia: Space-time ARIMA modeling

Abstract: The novel coronavirus COVID-19 is spreading across the globe. By 30 Sep 2020, the World Health Organization (WHO) announced that the number of cases worldwide had reached 34 million with more than one million deaths. The Kingdom of Saudi Arabia (KSA) registered the first case of COVID-19 on 2 Mar 2020. Since then, the number of infections has been increasing gradually on a daily basis. On 20 Sep 2020, the KSA reported 334,605 cases, with 319,154 recoveries and 4,768 deaths. The KSA has taken several measures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The spread of SARS-CoV-2 infection is detrimental, given its association with several parameters, including age and other underlying conditions [ 5 , 6 ]. A previous study found that patients with underlying health conditions carry a significantly higher risk of infection than healthy individuals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spread of SARS-CoV-2 infection is detrimental, given its association with several parameters, including age and other underlying conditions [ 5 , 6 ]. A previous study found that patients with underlying health conditions carry a significantly higher risk of infection than healthy individuals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awwad et al [84] used the statistical STARMA model to predict confirmed and death cases in Saudi Arabian cities. This study covered most Saudi Arabian cities in the time interval from 23 March 2020 to 28 May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the parametric estimates of saturated Engel curves of non-food expenditures categories, we found that the incidence of housing poverty is lower, while poverty incidence in the health and education expenditure categories is the highest, clarifying the importance of designing policies for unsatisfied needs that will ultimately contribute to improving households' living standards and reducing overall poverty rates in general. In future work, we plan to study the impact of the COVID-19 pandemic on non-food consumption in Egypt [42].…”
Section: Discussionmentioning
confidence: 99%